Chthonic Legal Traditions: A Standpoint Legal Research Paradigm for Comparative Analysis on Australian Indigenous Legal Orders - Maria Salvatrice Randazzo (Udayana Journal of Law and Culture, 2019)
In contemporary comparative legal scholarship, it is no longer controversial to assert the relevance of investigations into chthonic legal orders; however, there is a significant divergence on how they should be undertaken. The paper takes in consideration the Australian chthonic legal orders and argues that their investigations by non-Indigenous researchers need to be undertaken acknowledging an Indigenous epistemological approach to research, with methodological frameworks that, consistent with the principles of an Indigenous standpoint theory, aim to develop a legal standpoint research paradigm informed by Indigenous legal ontologies, epistemic theories and research practices. The research paradigm so elaborated is justified by the necessity of devising new epistemological models to guide understandings—and theoretical elaboration—of Australian Indigenous orders which are consistent and coherent with their ontological, epistemological and axiological universe.